Penilaian Tingkat Kesehatan Bank dengan Metode Risk Based Bank Rating pada PT. Bank Negara Indonesia Tbk Periode 2016-2020 - Atti Rasnawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study raises the issue of how to assess bank health using the Risk Based Bank Rating method with ratios of NPL, LDR, GCG, ROA, NIM and CAR at PT. Bank Negara Indonesia Tbk 2016-2020. The purpose of this study was to determine the soundness of Bank Negara Indonesia Tbk with the Risk Based Bank Rating method by looking at the conditions based on the annual financial statements. With the results of the NPL ratio having a value of less than 2%, which means that lending is more than non-performing loans, the LDR ratio with the criteria of 85%-100% which means it is quite healthy to fulfill its obligations, the GCG ratio is in level 2 condition, which is generally good, ROA ratio that asset management is in good condition, the NIM ratio is above 3%, which means a high level of income and a CAR ratio is above 12% in a very healthy condition, which means that capital is carried out very effectively.